(untitled) (PJDOL, 2023)
The primary achievement of distance and regular students is managing time effectively. Mismanagement disturbs the academic achievements of learners. Time administration plays a significant role in improving learners’ performance and accomplishments. It is a skill to manage timeand every learner must familiar and command on this skill for the sake of better results.